2021
DOI: 10.31234/osf.io/6f829
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring Individuals’ Misogynistic Attitudes: Development and Validation of the Misogyny Scale

Abstract: Across three studies based on a nationally representative survey (n = 1500), we developed and validated the misogyny scale. Initial items were generated from an extensive literature search and subsequently derived from validated scales assessing internalised misogyny, hostile sexism, and hostility towards women. Construct and measurement validity were established across several studies. An exploratory factor analysis (Study 1, n = 750) established the factor structure of the 10-item misogyny scale. In study 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Hypotheses 4 and 5, that authoritarianism scores and misogynistic attitude scores respectively would be negatively associated with environmental concern, were jointly tested using a standard multiple regression with simultaneous entry of all predictors. Gender was also included as a predictor as it is known to be associated with both Misogyny Scale and EIA‐24‐P scores (Milfont & Duckitt, 2010; Rottweiler & Gill, 2021). The analysis, summarized in Table 3, indicated that this set of variables predicted around 20% of variance in concern for protecting the environment (adjusted R 2 = .20).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hypotheses 4 and 5, that authoritarianism scores and misogynistic attitude scores respectively would be negatively associated with environmental concern, were jointly tested using a standard multiple regression with simultaneous entry of all predictors. Gender was also included as a predictor as it is known to be associated with both Misogyny Scale and EIA‐24‐P scores (Milfont & Duckitt, 2010; Rottweiler & Gill, 2021). The analysis, summarized in Table 3, indicated that this set of variables predicted around 20% of variance in concern for protecting the environment (adjusted R 2 = .20).…”
Section: Resultsmentioning
confidence: 99%
“…Misogynistic attitudes were measured using the Misogyny Scale (Rottweiler & Gill, 2021). This is a 10-item questionnaire which requires participants to respond to statements such as "Women seek to gain power by getting control over men" on a 7-point scale anchored at "Strongly Disagree" and "Strongly Agree."…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This could provide a more exhaustive picture of the consequences of violating gender stereotypes in different contexts. Relatedly, organizational cultures can make a difference; for instance, research has shown that in misogynistic contexts, people tend to see women as exploitative and manipulative, seeking to gain control over men (Rottweiler & Gill, 2020). Future research would benefit from investigating organizational culture as a moderator.…”
Section: Discussionmentioning
confidence: 99%